Вероятностно-математические модели образования информационных потоков в системе сигнализации о пожаре на воздушных судах - Аль-Аммори, А.; Дмитриченко, А.Н.; Аль-Аммори, Х.А (Проблемы управления и информатики, 2019)
Сформулированы понятия отказа функциональной системы как случайного отвлеченного события для авиационного оборудования и ВС в целом и увязки его с требованием норм технической документации по производству полетов в ожидаемых и экстремальных условиях эксплуатации. Разработана геометрически-вероятностная модель отказа, которая позволяет выделить зоны неопределенностей для анализа ошибок контроля ситуации с пожаром на воздушном судне как необнаружения и ложного срабатывания. Предложена вероятностно-математическая модель функционирования системы датчиков информации, применение которой позволяет существенно уменьшить отрицательные влияния физических недостатков отдельных источников информации на качество функционирования систем сигнализации о пожаре на воздушных судах. Вирішується актуальне завдання в авіаційній практиці, яке полягає в наданні екіпажу повітряного судна достовірної інформації від первинних джерел інформації (датчиків контрольованих параметрів) в нормальних і особливих польотних ситуаціях. Для вирішення цього завдання розроблено ймовірнісно-фізичну модель процесів утворення інформаційних потоків систем сигналізації про пожежу повітряних суден. Показано геометричні ймовірнісні характеристики: ймовірності правильного виявлення пожежі, невиявлення пожежі та помилкової тривоги. Математично доведено умови, які забезпечують одночасно рівний ступінь зниження ймовірностей невиявлення і помилкової тривоги, тобто щоб вони одночасно були рівними і мінімальними. Запропоновано розглянути систему пожежогасіння за допомогою структурної схеми графу стану інформаційно-резервованої системи. Проведено аналіз формування та утворення потоків контролю в системі сигналізації про пожежу та доведено, що системні ймовірності формують повну групу подій, яку в подальшому можна розглядати за допомогою математичних і ймовірнісних методів аналізу для прогнозування стану системи сигналізації про пожежу. Отримано математичні формули порівняння ймовірностей невиявлення і помилкової тривоги і показано їх графічні залежності відносно до ймовірності правильного виявлення та кількості датчиків у системі. Визначено математичну залежність коефіцієнта зростання ймовірності правильного виявлення пожежі порівняно з ймовірністю помилкової тривоги з урахуванням кількості датчиків. Доведено, що зі збільшенням кількості датчиків коефіцієнт зростання збільшується за експоненційною функцією. Тому в конкретних умовах можна загрубляти чутливість датчиків, підвищуючи поріг спрацьовування і при цьому зберігати умови, які забезпечують мінімальні значення ймовірностей невиявлення і помилкової тривоги систем сигналізації про пожежу. The article deals with solving the urgent problem for aviation practice, which is to provide the aircraft crew with reliable information from primary sources of information (sensors of controlled parameters) in normal and special flight situations. To solve this problem a probabilistic-physical model of the processes for formation of the information flows of aircraft's fire alarm system is developed. Geometric probabilistic characteristics are shown: the probabilities of correct fire detection, non-detection and false alarm. Mathematically proved conditions ensuring simultaneously equal degree of reducing the probabilities of non-detection and false alarm, i.e. when they are to be simultaneously equal and minimal. It is proposed to consider the fire extinguishing system using the structural diagram of the state graph of the information-reserve system. The analysis of the formation and creation of the control flows in the fire alarm system has been carried out and it has been proved that system probabilities form a complete group of events that can be later considered using mathematical and probabilistic analysis methods to predict the state of the fire alarm system. Mathematical formulas for comparing the probabilities of non-detection and false alarms are obtained and their graphical dependencies with respect to the probability of correct detection and the number of sensors in the system are shown. The mathematical dependence of the coefficient growth of the probability of a correct fire detection compared with the probability of a false alarm, taking into account the number of sensors is obtained. It is proved that with an increase in the number of sensors, the coefficient of growth increases in exponential function. Therefore, in specific conditions, it makes sense to decrease the sensitivity of the sensors, raising the response threshold, while maintaining the conditions for ensuring the minimum values of the probabilities of non-detection and false alarm of fire alarm systems.